2021
DOI: 10.22270/jddt.v11i3-s.4846
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factor of Chronic Rhinosinusitis and the Impact on Quality of Life in Students of the Medical Faculty Christian University of Indonesia in 2018

Abstract: Chronic Rhinosinusitis (CRS) is an inflammation of nasal mucose dan paranasal sinuses with ≥ two symptoms, one of which should be nasal blockage/ obstruction or nasal discharge (anterior/ posterior nasal drip) that happened for ≥ 12 Weeks. CRS affects 5-15% adult population in Europe and the United States of America, with a prevalence of 2-4% that doctors have diagnosed. The risk factors of CRS that quite often happened on CRS is allergic rhinitis. CRS also often happened in women. CRS also impact the patient'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In addition, the near location of the maxillary sinuses to the teeth in the mouth cavity make the spreading of odontogenic infections is easier. Different result was reported in previous studies that acute and chronic rhinosinusitis were more commonly found in women [5], [12]. The smaller size of sinus ostium in women than men was contributed to obstruction and mucous drainage obstruction of sinus, which increase the risk of rhinosinusitis.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, the near location of the maxillary sinuses to the teeth in the mouth cavity make the spreading of odontogenic infections is easier. Different result was reported in previous studies that acute and chronic rhinosinusitis were more commonly found in women [5], [12]. The smaller size of sinus ostium in women than men was contributed to obstruction and mucous drainage obstruction of sinus, which increase the risk of rhinosinusitis.…”
Section: Resultsmentioning
confidence: 56%
“…Untreated acute rhinosinusitis will lead to chronic rhinosinusitis. In addition, patients with comorbidities such as allergic rhinitis and asthma are also more prone to experiencing chronic rhinosinusitis which may cause a significant decrease in quality of life [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic rhinitis (CR), a frequent inflammatory condition of the sinuses and nasal passages, can greatly re-duce a person's ability to go about their everyday lives and their quality of life. 1 Nasal congestion and a runny nose that lasts for at least 12 weeks are typical symptoms. 2 However, topical and systemic steroid usage is essential to the management of this illness.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic rhinosinusitis is a syndrome that can be brought on by a variety of aetiologies that are complex and poorly understood. Chronic rhinosinusitis is predisposed by ciliary dysfunction, allergies, asthma, increased sensitivity to aspirin, immunocompromised, genetic, pregnancy, and endocrine factors, as well as local factors specific to the patient (host), biofilm-producing microorganisms, environmental factors, iatrogenic factors, Helicobacter pylori, laryngopharyngeal reflux, and osteitis [6] . Studies have shown that physiological and mental health-related quality of life is significantly low among patients with chronic rhinosinusitis, and a number of variables could contribute to the decline of the same.…”
Section: Introductionmentioning
confidence: 99%